Inflammatory Markers and the Risk of Chronic Obstructive Pulmonary Disease: A Systematic Review and Meta-Analysis. - Bin Su; Tiansheng Liu; Haojun Fan; Feng Chen; Hui Ding; Zhouwei Wu; Hongwu Wang; Shike Hou (PLoS ONE)
Systemic inflammatory factors are inconsistently associated with the pathogenesis of chronic obstructive pulmonary disease (COPD). We conducted a systematic review and meta-analysis to summarize the evidence supporting the association between systemic inflammation and the risk of COPD. Pertinent studies were retrieved from PubMed, EmBase, and the Cochrane Library until April 2015. A random-effects model was used to process the data, and the analysis was further stratified by factors affecting these associations. Sensitivity analyses for publication bias were performed. We included 24 observational studies reporting data on 10,677 COPD patients and 28,660 controls. Overall, we noted that COPD was associated with elevated serum CRP (SMD: 1.21; 95%CI: 0.92-1.50; P < 0.001), leukocytes (SMD: 1.07; 95%: 0.25-1.88; P = 0.010), IL-6 (SMD: 0.90; 95%CI: 0.48-1.31; P < 0.001), IL-8 (SMD: 2.34; 95%CI: 0.69-4.00; P = 0.006), and fibrinogen levels (SMD: 0.87; 95%CI: 0.44-1.31; P < 0.001) when compared with control. However, COPD was not significantly associated with TNF-α levels when compared with control (SMD: 0.60; 95%CI: -0.46 to 1.67; P = 0.266). Our findings suggested that COPD was associated with elevated serum CRP, leukocytes, IL-6, IL-8, and fibrinogen, without any significant relationship with TNF-α.